Attenuation of haemodynamic response during intubation with glidescope® video laryngoscope using either lignocaine or magnesium; a randomized clinical study - Ahmad Afifi, Mohd Arshad (Universiti Sains Malaysia, 2010)
Intubation with Glidescope Videolaryngoscope (GSVL) has been associated with longer period of pressor response. This study aimed to look at haemodynamic parameters (SBP, DBP, HR, MAP) during laryngoscopy and intubation using GSVL with either Lignocaine or Magnesium used to attenuate the pressor response. Methodology: 82 patients planned for general anesthesia with endotracheal intubation were recruited. They were blinded, and randomized into 2 groups; Lignocaine (A) and Magnesium (B). The agents were given at 1.5mg/kg and 40mg/kg respectively in group A and B, and each diluted into 20ml syringe and given IV over 5min before induction. Inductions were standardized with IV Propofol 2mg/kg, IV Fentanyl Imcg/kg and IV Rocuronium 1 mg/kg. A single intubator with experience in GSVL performed the intubations. Haemodynamic parameters were collected at baseline, post induction, at intubation, 1, 3, 5 and 10 minutes post intubation. The interaction of haemodynamic parameters within and between groups were tested with repeated measure ANCOVA. Result: There were significant interaction between time during intubation and estimated marginal mean of DBP, MAP and HR in both groups (p<0.05). The changes in estimated mean DBP and MAP were constantly less than baseline value post induction and intubation. However the rise in HR at Imin postintubation in Magnesium group was 11% above baseline and required 5 minutes to return to baseline (p<0.05). The interaction in SBP is not significant (p>0.05). XV Conclusion: Magnesium at 40mg/kg is less effective than lignocaine in attenuating pressor response to intubation with GSVL. XVI